2019
DOI: 10.1371/journal.pone.0221814
|View full text |Cite
|
Sign up to set email alerts
|

To eat or not to eat: Reward delay impulsivity in children with loss of control eating, attention deficit / hyperactivity disorder, a double diagnosis, and healthy children

Abstract: Reward delay impulsivity is a feature of attention deficit/hyperactivity disorder (ADHD) and a likely feature of loss of control eating (LOC-E), which might explain the higher risk of children with ADHD or LOC-E to become obese. The goal of this study was to investigate reward delay impulsivity in children with LOC-E, ADHD, or a double diagnosis, in contrast to healthy children. Children (8 to 13 years) with LOC-E (n = 24), ADHD (n = 33), a double diagnosis (n = 9), and healthy children (n = 34) performed a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…This selection process resulted in the full-text examination of 19 articles, of which 7 articles were excluded for the following reasons: (a) they did not present data regarding the associations between LOC-eating and inhibitory control and/or reward sensitivity in the results, conclusion, or discussion sections ( n = 4); (b) they presented a global measure of eating behavior psychopathology, but did not explicitly evaluate LOC-eating ( n = 1); (c) they assessed general executive functioning rather than inhibitory control/reward sensitivity scores ( n = 1); and (d) the results regarding the relationship between LOC-eating and inhibitory control did not contain any data for the sample without attention-deficit/hyperactivity disorder. Therefore, a total of 12 articles were included in this review [ 18 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This selection process resulted in the full-text examination of 19 articles, of which 7 articles were excluded for the following reasons: (a) they did not present data regarding the associations between LOC-eating and inhibitory control and/or reward sensitivity in the results, conclusion, or discussion sections ( n = 4); (b) they presented a global measure of eating behavior psychopathology, but did not explicitly evaluate LOC-eating ( n = 1); (c) they assessed general executive functioning rather than inhibitory control/reward sensitivity scores ( n = 1); and (d) the results regarding the relationship between LOC-eating and inhibitory control did not contain any data for the sample without attention-deficit/hyperactivity disorder. Therefore, a total of 12 articles were included in this review [ 18 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the children with comorbid diagnoses were most likely to worry about losing control over eating during the task. These ndings suggest that a lack of behavioral inhibition (to food reward) in children with ADHD is a relevant factor in the drive to eat prematurely [10].…”
Section: Introductionmentioning
confidence: 85%
“…This study also found that children with LOC-E are more likely to exhibit high impulsivity on a neurobehavioral task (Go/No Go) and parent-rated scale compared to healthy controls. Another study used a delay of grati cation task (DoGT) in children with ADHD or LOC-E, comorbid diagnoses (ADHD and LOC-E), and healthy controls [10]. They found that children with ADHD and comorbid diagnoses had signi cantly higher risk of eating prematurely during the DoGT compared to children with only LOC-E or healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…This study also found that children with LOC-E are more likely to exhibit high impulsivity on a neurobehavioral task ( Go/No Go ) and parent-rated scale compared to healthy controls. Another study used a delay of gratification task (DoGT) in children with ADHD or LOC-E, comorbid diagnoses (ADHD and LOC-E), and healthy controls [ 10 ]. They found that children with ADHD and comorbid diagnoses had significantly higher risk of eating prematurely during the DoGT compared to children with only LOC-E or healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the children with comorbid diagnoses were most likely to worry about losing control over eating during the task. These findings suggest that a lack of behavioral inhibition (to food reward) in children with ADHD is a relevant factor in the drive to eat prematurely [ 10 ].…”
Section: Introductionmentioning
confidence: 99%